Predictive Testing of Seafood Cans and Pouches by Electrochemical Impedance Spectroscopy - Ashraf. P., Muhamed; C.N., Ravishankar (Fishery Technology, 2025)
Studies were conducted to evaluate the performance of retortable pouches and coated food cans using Electrochemical Impedance Spectroscopy (EIS). New unused retortable pouches and tin free steel cans were compared with the corresponding processed seafood cans for impedance. The pore resistance (Rp) of lids of tin free steel cans was reduced significantly on storage compared to the body which implies that the former was more susceptible for corrosion and deterioration. Processed retort pouches were superior to cans after two years of storage, which follows equivalent circuit RC. See-through pouches have about 2% reduction in pore resistance after thirteen months compared to the unused pouches The results reveal that EIS studies can be used for predicting the quality of cans and pouches